The Economics of Convention. - Young, H (1996)
The purpose of conventions is to coordinate people's expectations in economic and social interactions that have multiple equilibria. Conventions often emerge endogenously from the accumulation of many precedents, a process that can be modeled as a stochastic dynamical system. The theory leads to specific predictions about the ways in which conventions form and are displaced, and identifies key properties of conventions that are most likely to withstand the test of time. The theory is illustrated by the evolution of left-wing driving conventions in Europe and patterns of sharecropping contracts in agriculture.